Rhizopus oligosporus Activity in Crude Extract and Powder Form to Reduce Aspergillus flavus and Aflatoxin Contamination in Corn - Eni Kusumaningtyas; - Masrianti; F Fitrya (Jurnal Ilmu Ternak dan Veteriner, 2019)
Rhizopus oligosporus (RO) in isolate culture was known to reduce contamination toxigenic mold Aspergillus flavus (AF) and aflatoxin B1 in chicken feed. Application in culture form was not effective. The aim of this research was to evaluate RO activities in extract and inoculum form to reduce contamination of AF and aflatoxin B1 in corn. RO was harvested from agar plate, blended, added with water (ratio 1:1 (w/v)) and centrifuged. Supernatant was filtered using Whatman 41. Inoculum was made by inoculation RO in soy powder and incubated at 28oC for 5 days. Inoculum was dried at 40oC for 24-28 hours. Assay was conducted by addition extract or inoculum to corn. Extract and corn ratio were 1:1 (v/w), while inoculum doses were 5, 25, 50, 1000 dan 200 g/kg corn. Assay for aflatoxin B1 was done using kit ELISA aflatoxin. The result of this research showed that extract was able to reduce AF contamination up to 1 log 10, while the less concentration of inoculum which able to inhibit AF up to 6 log 10 was 100 g/kg corn. Extract RO 125 and 250 mL/kg corn was able to reduce aflatoxin contamination by 93.69 % and 85.84 %. Inoculum at dose 5 and 100 g/kg corn was able to reduce aflatoxin 57.58% and 85%. Based on the result, it could be concluded that RO in extract or inoculum form was able to reduce contamination of AF and aflatoxin B1 in corn. Rhizopus as inoculum was easier to be applied than in extract form.